IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL DAN PENGARUHNYA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KOTA PADANG PANJANG - Yuki Fitria (Jurnal Praktik Bisnis, 2016)
This research aims to analyze the effect of transformational leadership to employees’ job statisfaction at the Dinas Pekerjaan Umum the city of Padang Panjang. Objects in this study were employees of the Dinas Pekerjaan Umum the city of Padang Panjang, West Sumatra. The population in this study were all employees at the Dinas Pekerjaan Umum of Padang Panjang, as many as 68 people. The sampling technique used is total sampling technique, the sample in this study amounted to 68 people. The data analysis technique is a simple regression using SPSS. The results showed that transformational leadership significant and positive impact on job satisfaction of employees in the Dinas Pekerjaan Umum Padang Panjang.Keywords: transformational leadership and job satisfaction